2022
DOI: 10.3390/molecules27248652
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigating the Preferential Enrichment of DL-Arginine Fumarate: New Thoughts on the Mechanism of This Far from Equilibrium Crystallization Phenomenon

Abstract: Preferential enrichment (PE) is a crystallization process, starting from either a racemic of slightly enantio-enriched solution (ca. +5%) that results in a high enantiomeric excess in the liquid phase (>+90%ee) and a slight opposite excess in the deposited crystals (−2 to −5%ee). The mechanism(s) of this symmetry-breaking phenomenon is (are) still a matter of debate since it eludes rationalization by phase diagram formalism. In this publication, we thoroughly reinvestigate the PE phenomenon of arginine fuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Furthermore, with the addition of 10 mL 13 C 6 -labeled L-Arg enantiomer solution (0.1 wt% of the total DL-Arg), despite the completion of PE, 13 C 6 labeled molecules could still be found in the crystal phase. 198 These results showed that PE of DL-Arg$fumaric acid is only driven by the material exchange between the solution and crystals under high supersaturation, rather than polymorphic transition (Fig. 10c).…”
Section: Reviewmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, with the addition of 10 mL 13 C 6 -labeled L-Arg enantiomer solution (0.1 wt% of the total DL-Arg), despite the completion of PE, 13 C 6 labeled molecules could still be found in the crystal phase. 198 These results showed that PE of DL-Arg$fumaric acid is only driven by the material exchange between the solution and crystals under high supersaturation, rather than polymorphic transition (Fig. 10c).…”
Section: Reviewmentioning
confidence: 85%
“…Thus, the crystal engineering strategy can impart Racs with unique intermolecular interactions, packing modes and polymorphism, leading to a different 194 (c) PE mechanism of the DL-Arg$fumaric acid cocrystal. 198 PE mechanism. In 2023, the recapture of a second-generation cocrystal, DL-Arg$fumaric acid, further raised doubts about the necessity of the polymorphic transformation.…”
Section: Preferential Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, enantioenriched domains must develop without facing an enormous energy cost or the presence of a solid solution in proximity to the racemic arrangement. 72…”
Section: Crystallization-based Techniquesmentioning
confidence: 99%
“…While various resolution methods are available (chromatography and membrane separation), crystallization is an attractive technique due to the high degree of chiral discrimination achievable during molecular self-assembly. If there are few examples of enantiomeric separation based on crystallization applied to molecules forming stable racemic compounds, in most cases, accessing a conglomerate is a prerequisite (i.e., the two enantiomers must crystallize in separate crystals, each being enantiopure). This is applicable to preferential crystallization (PC), an out-of-equilibrium stereoselective crystallization process occurring via seeding.…”
Section: Introductionmentioning
confidence: 99%